2005
DOI: 10.22621/cfn.v119i4.177
|View full text |Cite
|
Sign up to set email alerts
|

Breeding and Non-Breeding Range of Canada, <em>Branta canadensis</em>, and Cackling Geese, <em>Branta hutchinsii</em>, in the Eastern Canadian Arctic

Abstract: The accepted breeding distribution of Canada Geese from the Atlantic Population (Branta canadensis interior) in the eastern Canadian Arctic is currently confined to northern Québec and the south coast of Baffin Island. Here we provide evidence based on observations from scientific studies, Inuit hunters, and territorial Wildlife Officers that B. c. interior now breeds in growing numbers 500 km farther north on northeastern Baffin Island than previously reported. Cackling Geese (B. hutchinsii), which breed more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…This account provides conclusive evidence to support earlier observations of nesting by Canada Geese in the eastern Arctic of North America (e.g., Sutton, 1932;Soper, 1946;Cooch, 1977;Mallory et al, 2005). As far as we know, this is the northernmost confirmed nesting record for Canada Geese in North America.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This account provides conclusive evidence to support earlier observations of nesting by Canada Geese in the eastern Arctic of North America (e.g., Sutton, 1932;Soper, 1946;Cooch, 1977;Mallory et al, 2005). As far as we know, this is the northernmost confirmed nesting record for Canada Geese in North America.…”
Section: Discussionsupporting
confidence: 89%
“…Norment et al (1999) reported observations of Canada Geese accompanied by goslings in the forest-tundra transition between 62.4˚ N, 104.8˚ W and 64.6˚ N, 100.5˚ W and mentioned separately that a small subspecies nested in this area on cliffs along the Clarke River, but they did not provide any other information. Mallory et al (2005) reported anecdotal evidence of nesting (large-bodied) Canada Geese from several locations on Baffin Island that was based on observations by Inuit hunters, wildlife officers, and scientific investigators. Despite numerous observations, there was no conclusive scientific evidence (e.g., photographs, measurements of adult geese or their eggs, genetic materials collected from eggs, nests, or pre-fledging goslings) to verify that Canada Geese, and not Cackling Geese, had nested in any of these cases.…”
Section: Introductionmentioning
confidence: 99%